KARAKTERISTIK “AT-TAFSIR AL-HADITS” KARYA MUHAMMAD IZZAT DARWAZAH - Setyawan (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2023)
Few of the mufassirs present their commentary products based on the order in which the surahs were descended, causing them to be less familiar and seem to have lost the historical and contextualized side when the surahs and verses were revealed to the prophet Muhammad. This is what prompted Muhammad Izzat Darwazah to come up with a product of interpretation based on the order in which the surah "at-tafsîr al-Hadîts" was descended. In this interpretation, there are 9 characteristics of interpretation, which become the principles of interpretation, showing the accuracy and concern for the purity of the meanings of the verses of the Qur'an, not merely prioritizing ratios but also based on justifiable arguments. It's just that this interpretation only understands the Qur'an in its historical and literal context, not trying to project it onto the present situation.